2002
DOI: 10.1183/09031936.02.01182001
|View full text |Cite
|
Sign up to set email alerts
|

Traffic-related air pollution and respiratory health during the first 2 yrs of life

Abstract: As part of an international collaborative study on the impact of TrafficRelated Air Pollution on Childhood Asthma (TRAPCA), the health effects associated with long-term exposure to particles with a 50% cut-off aerodynamic diameter of 2.5 mm (PM2.5), PM2.5 absorbance, and nitrogen dioxide (NO 2 ) were analysed.The German part of the TRAPCA study used data from subpopulations of two ongoing birth cohort studies (German Infant Nutrition Intervention Programme (GINI) and Influences of Lifestyle Related Factors on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
157
4
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 247 publications
(182 citation statements)
references
References 33 publications
(72 reference statements)
18
157
4
3
Order By: Relevance
“…In a collaborative study, within-city contrasts in PM 2.5 , black smoke and NO 2 were examined and modelled to provide exposure assessment for ongoing epidemiologic studies on development of allergy and asthma in young children (Brauer et al, 2003). Significant associations have been reported from these studies so far on symptoms of wheeze, upper and lower respiratory symptoms, allergic sensitisation and otitis media (Brauer et al, 2002(Brauer et al, , 2006(Brauer et al, , 2007Gehring et al, 2002;Morgenstern et al, 2007). Table 3 provides some quantitative effect estimates from these studies expressed per 10 mg/m 3 NO 2 .…”
Section: Morbiditymentioning
confidence: 99%
“…In a collaborative study, within-city contrasts in PM 2.5 , black smoke and NO 2 were examined and modelled to provide exposure assessment for ongoing epidemiologic studies on development of allergy and asthma in young children (Brauer et al, 2003). Significant associations have been reported from these studies so far on symptoms of wheeze, upper and lower respiratory symptoms, allergic sensitisation and otitis media (Brauer et al, 2002(Brauer et al, , 2006(Brauer et al, , 2007Gehring et al, 2002;Morgenstern et al, 2007). Table 3 provides some quantitative effect estimates from these studies expressed per 10 mg/m 3 NO 2 .…”
Section: Morbiditymentioning
confidence: 99%
“…The disease is now reaching epidemic proportions in westernized countries. Living in high traffic areas and exposure specifically to diesel exhaust particles (DEP) have been associated with increased respiratory symptoms and impaired lung function in children [17][18][19][20][21]. DEP is formed mainly of elemental carbon particles to which organic compounds, including polycyclic aromatic hydrocarbons (PAH) are absorbed.…”
Section: Preparation Of Pah Samplesmentioning
confidence: 99%
“…Additional support for the important role which endotoxin exposure might play comes from a cross-sectional study, which found an association between exposure to higher levels of house-dust endotoxin with lower prevalence of allergic sensitisation in children [30]. However, other factors than indoor exposure might also be involved in the development of atopic disease [31,32].…”
mentioning
confidence: 99%